Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-42773-y
|View full text |Cite
|
Sign up to set email alerts
|

CD271 is a molecular switch with divergent roles in melanoma and melanocyte development

Abstract: Dysregulation of signaling networks controlling self-renewal and migration of developmental cell lineages is closely linked to the proliferative and invasive properties of tumors. Identification of such signaling pathways and their critical regulators is vital for successful design of effective targeted therapies against neoplastic tissue growth. The neurotrophin receptor (CD271/NGFR/p75NTR) is a key regulator of the melanocytic cell lineage through its ability to mediate cell growth, survival, and differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
2
23
1
Order By: Relevance
“…2c, d ). Taken together, these results indicate that NGFR is essential for proliferation, survival, and colony formation of MIC cells we isolated here, which is in agreement with previous studies 16 , 17 .
Fig.
…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…2c, d ). Taken together, these results indicate that NGFR is essential for proliferation, survival, and colony formation of MIC cells we isolated here, which is in agreement with previous studies 16 , 17 .
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…Its high level was associated with melanoma progress in a clinical case study 23 , although another study suggested that its protein is unstable and thus might not be an ideal biomarker for human melanoma clinically 24 . Most recently, a clinical gene profiling study suggested that NGFR might play a divergent role in melanocyte and melanoma development through two different signaling pathways 17 . These studies highlight the importance of NGFR in MICs' renewal, proliferation, and derived tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1A). This high ENPP2 expression is unrelated to gene amplification or activation of oncogenic pathways (https://www.cbioportal.org) but rather reflects high ATX expression observed in normal melanocytes (Filipp et al, 2019) and results not shown). Remarkably, however, ENPP2 expression in cancer cells correlates rather poorly with that in the corresponding tumors (Suppl.…”
Section: Resultsmentioning
confidence: 93%